Studi komparatif nilai kondisi perkerasan lentur di Ruas Jalan Sekargadung–Sidomulyo berdasarkan metode PCI dan SDI - Dafin Farianto; Sugeng Dwi Hartantyo; Romadhon (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Public mobility and regional economic growth are heavily dependent on the quality of road infrastructure. However, high and repetitive traffic loads frequently trigger premature failure in flexible pavements. This study aims to identify the types and severity levels of distress, assess pavement conditions, and formulate maintenance recommendations for the Sekargadung-Sidomulyo road section in Gresik, East Java. Pavement condition assessment was conducted using the Pavement Condition Index (PCI) and Surface Distress Index (SDI) methods. The distresses identified in the field include depressions, rutting, patching, alligator cracking, bleeding, shoving, longitudinal cracking, potholes, raveling, block cracking, joint reflection cracking, and bumps. The results indicate an average PCI value of 69.3 and an SDI value of 49.5, both consistently classifying the road condition as "Good." Nonetheless, PCI proved to be superior in providing a comprehensive evaluation, as it accounts for detailed distress types, severity levels, and affected areas. The primary contribution of this research is providing a comparative model between the PCI and SDI methods that validates the accuracy of field data. Ultimately, the output of this study serves as a practical decision-making tool for relevant authorities in determining efficient road maintenance priorities.